Based on small molecules: development and application of fibroblast activation protein inhibitors radiopharmaceutical in tumor precision therapy - Luo, Yihui; Fu, Haitian; Yu, Chunjing (Frontiers in Pharmacology, 2025)
The discovery of biomarkers for malignant tumors is driving the development of new radiopharmaceuticals in nuclear medicine. The development and optimization of novel radiopharmaceuticals to occupy an increasingly important role in tumor diagnosis and treatment. In recent years, fibroblast activation protein (FAP) has gained attention as a promising tumor target due to its widespread expression across various tumors. FAP inhibitor (FAPI) radiopharmaceuticals are considered to be the most promising to be developed for targeting FAP due to their rapid and specific tumor targeting. This review briefly outlines the developmental history of FAP-targeted small-molecule enzyme activity inhibitors, highlighting the effective role of targeting molecules, linkers, and certain functional groups in the delivery of radioisotopes to cancerous tissues. These development strategies will serve as a reference for the further development and application of relevant radiopharmaceuticals. This review also delineates the progress on clinical FAPI as a radioisotope delivery vehicle for the targeted radioligand therapy of tumors and introduces the latest combination therapy involving FAPI radiopharmaceutical for tumor treatment. The findings provide novel therapeutic insights into the targeted radioligand therapy of tumors.